The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1967
DOI: 10.1104/pp.42.1.144
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Requirements for the Biological Activity of Ethylene

Abstract: Summary. The molecular requirements for ethylene action were investigated using the pea straight growth test. Biological activity requires an unsaturated bond adjacent to a terminal carbon atom, is inversely related to molecular size, and is decreased by substitutions which lower the electron densitv in the unsaturated position. Evidence is presented that ethylene binds to a metal containing receptor site. 002 is a competitive inhibitor of ethylene action, and prevents high concentrations of auxin (which stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
285
0
14

Year Published

1968
1968
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 559 publications
(317 citation statements)
references
References 21 publications
(12 reference statements)
13
285
0
14
Order By: Relevance
“…Indeed CO 2 stimulates ACC-oxidase activity in vitro with an optimal in the range of 2 kPa (John 1997). However, at higher partial pressures, CO 2 acts as a competitive inhibitor of ethylene action (Burg and Burg 1967). In accordance with these observations, there are other results such as the use of CO 2 partial pressures up to 5 kPa to inhibit ACC-oxidase and ACC-synthase (Bufler 1986) as well as the induction of mRNA (Gorny and Kader 1996).…”
Section: Resultssupporting
confidence: 56%
“…Indeed CO 2 stimulates ACC-oxidase activity in vitro with an optimal in the range of 2 kPa (John 1997). However, at higher partial pressures, CO 2 acts as a competitive inhibitor of ethylene action (Burg and Burg 1967). In accordance with these observations, there are other results such as the use of CO 2 partial pressures up to 5 kPa to inhibit ACC-oxidase and ACC-synthase (Bufler 1986) as well as the induction of mRNA (Gorny and Kader 1996).…”
Section: Resultssupporting
confidence: 56%
“…The inhibitory effect of CO 2 on auto-induced ethylene production in climacteric fruits could be due to competition between CO 2 and ethylene for the same active site (Burg and Burg 1967;Mathooko et al 1995). As per Burg and Burg (1967), the amount of CO 2 in the intercellular spaces of fruits at pre-climacteric stage is low but this may approach to higher levels of around 10% during ripening and post-climacteric phase. This higher endogenous level of CO 2 probably raises the threshold concentration of ethylene to higher levels for its action in fruits.…”
Section: High Carbon Dioxidementioning
confidence: 98%
“…2). It has already been reported that O 2 is required for the synthesis as well as the action of ethylene in fruits including tomato (Burg and Burg 1967). Fruits show reduction in respiration with lowering of O 2 in the surrounding atmosphere and at specific reduced level of O 2 there is induction of anaerobic respiration which leads to fast breakdown of sugars and this is named as the Pasteur effect (Kader 1986;Boersig et al 1988).…”
Section: Oxygen and Carbon Dioxidementioning
confidence: 99%
“…This model is possible, but two lines of evidence argue somewhat against it. First, it would not explain the lack of root swelling in various ethylene biosynthesis mutants; second, it is probable that, similar to ETR1 and its paralogs, any additional ethylene receptor would be blocked by silver ion (Burg and Burg, 1967), and thus silver should, but does not, revert the fei1 fei2 phenotype. A final model that is consistent with the data is that ACC itself, rather than ethylene, acts as a signaling molecule to regulate cell expansion in the FEI/SOS5 pathway.…”
Section: Role Of Acs5 In the Sos5/fei Pathwaymentioning
confidence: 99%